P366 genomics analysis and differentiation of Crohn's Disease, Intestinal Tuberculosis and Primary Intestinal Iymphoma. (30th January 2023) - Lin, L; Qu, Y; Zhao, X
Abstract: Background: Crohn's disease(CD), intestinal tuberculosis(ITB) and primary Intestinal Lymphom(PIL) are very similar in many aspects, and differential diagnosis of them remains a major clinical challenge. The purpose of this study is to perform genomic analysis of tissue wax blocks in patients by DASL analysis and screen out potential diagnostic genes for diseases. Methods: Tissue wax blocks from 31 patients with CD, 33 patients with ITB, 25 patients with PIL and 12 healthy controls were collected to detect the expression of genes in the samples by DASL analysis. The data were then normalized, followed by differential expression analysis and GO and KEGG enrichment analysis. Based on the above results, potential diagnostic genes are screened out and then verified by immunohistochemistry. Results: We obtained the expression intensity of 19869 genes in the intestinal tissues of 4 groups of patients. By differential expression analysis, the differentially expressed genes(DEGs) between these four groups of samples were obtained. GO and KEGG enrichment analysis showed that these DEGs had different effects on metabolic function, immune response, chemotaxis, growth and development, etc. According to the DEGs between the groups screened earlier, combined with the results of KEGG enrichment analysis, a total of seven potential diagnostic genes were screened, included EPHB3, CD70, CHST10, CXCL13, CEL, SCGB2A1 and SCGLEC10. Finally, the significant upregulation of EPHB3 in the intestinal mucosa of CD patients was verified by immunohistochemistry. Conclusion: CD, ITB and PIL have significant differences in genome expression, and EPHB3 has been confirmed to be significantly upregulated in CD, which is expected to become one of the indicators for disease differential diagnosis. At the same time, Based on the results of our GO enrichment analysis and the results of previous researchers, we believe that EPHB3 may participate in the occurrence and development of Crohn's disease through the regulation of the development of the digestive tract and digestive system, cell adhesion, and epithelial-to-mesenchymal transition.